Formation of Aminocyclopentadienes from Silyldihydropyridines: Ring Contractions Driven by Anion Stabilization. (26th April 2018) - Walker, Morgan M.; Chen, Shuming; Mercado, Brandon Q.; Houk, K. N.; Ellman, Jonathan A.
Abstract: Highly functionalized aminocyclopentadienes can be formed through the rearrangement of anions generated from readily prepared 6‐silyl‐1, 2‐dihydropyridines by desilylation with fluoride. The scope and generality of the reaction was defined, and diverse transformations were performed on the highly functionalized products. A mechanism and driving force for the rearrangement were identified from experiments and DFT calculations. Abstract : Dicht funktionalisierte Aminocyclopentadiene sind durch anionische Umlagerung von 6‐Silyl‐1, 2‐dihydropyridinen zugänglich. DFT‐Rechnungen wurden durchgeführt, um den Reaktionsmechanismus aufzuklären.